ASSESSING INDONESIA-CHILE BILATERAL TRADE OPPORTUNITIES: A REVEALED COMPARATIVE ADVANTAGE APPROACH - Sulthon Sjahril Sabaruddin; Hartanti Nugrahaningsih (Economic Journal of Emerging Markets, 2013)
AbstractThis paper analyzes the Indonesia-Chile bilateral trade opportunities based on their respective export competitiveness uses the Revealed Comparative Advantage Index for 2012. It finds that in general Indonesian exports to Chile are based on its comparative advantage, but the current exports still do not reflect its potential as most of the top ten Indonesian commodities with the strongest comparative advantage still do not able to penetrate the Chilean market. Meanwhile, the majority of the top-ten Chilean exports to Indonesia are based on its comparative advantage. Thus, both nations can still enhance bilateral trade relations particularly concerning with boosting trade relations based on their comparative advantage.Keywords: Comparative Advantage, Export Competitiveness, Bilateral TradeJEL classification numbers: F14, F15, F17AbstrakMakalah ini menganalisis peluang perdagangan bilateral Indonesia-Chile berdasarkan daya saing ekspor masing-masing negara menggunakan index Revealed Comparative Advantage untuk 2012. Paper ini menemukan bahwa, secara umum, ekspor Indonesia ke Chile didasarkan pada keunggulan komparatif, tetapi ekspor saat ini masih belum mencerminkan semua potensi ekspornya karena kebanyakan dari sepuluh komoditas Indonesia dengan keunggulan komparatif terkuat masih belum mampu menembus pasar Chili. Sementara itu, sebagian besar dari sepuluh-besar ekspor Chili ke Indonesia telah didasarkan pada keunggulan komparatif. Dengan demikian, kedua negara masih bisa meningkatkan hubungan perdagangan bilateral terutama terkait dengan upaya perdagangan berdasarkan keunggulan komparatif masing-masing negara.Keywords: Keunggulan komparatif, daya saing ekspor, perdagangan bilateralJEL classification numbers: F14, F15, F17